Hydrophilic, Breathable, and Washable Graphene Decorated Textile Assisted by Silk Sericin for Integrated Multimodal Smart Wearables. (18th March 2022) - Liang, Xiaoping; Zhu, Mengjia; Li, Haifang; Dou, Jinxin; Jian, Muqiang; Xia, Kailun; Li, Shuo; Zhang, Yingying
Abstract: Achieving integrated systems with comfortability and durability comparable to traditional textiles is one of the ultimate pursuits of smart wearables. This work reports a hydrophilic, breathable, biocompatible, and washable graphene‐decorated electronic textile that is achieved with the assistance of silk sericin and enables the fabrication of comfortable and integrated multisensing textiles. The graphene‐decorated textile is prepared by dyeing commercial textile with an aqueous graphene ink, which contains natural silk sericin‐coated graphene and is free of any artificial chemicals. The conformally coated hydrophilic sericin–graphene flakes and the well‐reserved knitted structure endow the textile with good conductivity, excellent hydrophilicity, biocompatibility, breathability, and flexibility, ensuring its electronic performance and wearing‐comfort. Moreover, the obtained textile is washable after processed with a cross‐linking agent. Based on the obtained textile, an integrated multisensing textile that can simultaneously collect and analyze myoelectrical and mechanical signals is developed, enabling the recognition and distinguishment of complex human motions. With the combined features of hydrophilicity, breathability, biocompatibility, washability, and versatility, this strategy of fabricating electronic textiles based on conventional textiles and an aqueous sericin–graphene ink provides a scalable and sustainable way to construct smart wearables. Abstract : A hydrophilic, breathable, biocompatible, and washable graphene‐based electronic textile is prepared using a green sericin–graphene aqueous ink. The textile is further used for fabrication of an integrated multimodal sensing textile, which can simultaneously collect mechanical strain signals myoelectrical signals, enabling recognizing of complex human motions.